1985
DOI: 10.1002/cjce.5450630109
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional heat, mass and flow phenomena in gas stirred reactors

Abstract: Computations are presented for multi‐dimensional flows in gas‐stirred liquids contained in vertical cylindrical vessels. Mass, momentum, energy and concentration equations were solved for the buoyancy driven transient flows under investigation. Turbulence was simultated by using zero order and differential models of turbulence. The use of convective and diffusive time scales was analyzed. Reasonable agreement with available experimental data was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The previous solutions had not considered the effect of rotation on turbulence and the three-dimensional flow induced by the baffles except that a "drag term" was purposely added in the angular momentum equation in the two-dimensional solution by Harvey and Greaves (1982) to reduce the tangential velocity and increase the axial velocity, Accordingly, a turbulence model which can account for the threedimensional characteristics of this flow field was needed. The nonisotropic viscosity model developed in this study should be beneficial to studies of the turbulent flow field in other types of mixing vessels such as tubular reactors, Berker and Whitaker (1978); gas stirred reactors, Salcudean et al (1985); and jet-stirred reactors, Liu and Barkelew (1986).…”
mentioning
confidence: 99%
“…The previous solutions had not considered the effect of rotation on turbulence and the three-dimensional flow induced by the baffles except that a "drag term" was purposely added in the angular momentum equation in the two-dimensional solution by Harvey and Greaves (1982) to reduce the tangential velocity and increase the axial velocity, Accordingly, a turbulence model which can account for the threedimensional characteristics of this flow field was needed. The nonisotropic viscosity model developed in this study should be beneficial to studies of the turbulent flow field in other types of mixing vessels such as tubular reactors, Berker and Whitaker (1978); gas stirred reactors, Salcudean et al (1985); and jet-stirred reactors, Liu and Barkelew (1986).…”
mentioning
confidence: 99%
“…[12] and [13] represents the contribution due to phase-mass diffusion, and ⌫ k and ⌫ ε are diffusion coefficients expressed as t ⌫ ϭ ϩ [14] k l k t ⌫ ϭ ϩ [15] ε l ε in which k and ε are Schmidt numbers for k and ε, respectively, whose values have been established and widely applied. [25] The last terms of Eqs.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…The early approaches [14,15] relied on a priori specification of the plume shape to simplify the problem. However, several studies [9,[16][17][18][19] have confirmed the significance of accurately representing the plume shape, especially when extrapolating from aqueous to metallic systems.…”
Section: Introductionmentioning
confidence: 99%
“…For the closure of momentum equations, concept of eddy viscosity is generally employed. Deb Roy et al (1978), Melville & Bray (1979), Sato et al (1981), Sahai & Guthrie (1982), Salcudean et al (1985) and Clark et al (1987) have proposed some empirical formulae for estimating effective turbulent viscosity in two-phase flows. However these equations prescribe a unique value of turbulent viscosity for the entire flow field and therefore fail to simulate effects of its variation within the system.…”
Section: Turbulene In Gas-liquid Flowsmentioning
confidence: 99%